ENHANCEMENT EFFECT OF PLASMA-ENHANCED CHEMICAL-VAPOR-DEPOSITED SIN CAPPING LAYER ON DIELECTRIC CAP QUANTUM-WELL DISORDERING - CHOI, WJ; LEE, S; ZHANG, JM; KIM, Y; KIM, SK; LEE, JI; KANG, KN; CHO, K (JAPAN SOC APPLIED PHYSICS, 1995)
Quantum well disordering of GaAs/AlGaAs multiple quantum well(MQW) has been accomplished with only plasma enhanced chemical vapor deposited (PECVD) SiN cap layer growth. The amount of blue shift increases with SiN growing time. This result has been explained by the vacancy indiffusion during PECVD SiN growth. Rapid thermal annealing (RTA) of the sample after SiN cap layer growth at 850 degrees C for 35 s caused a larger amount of blue shift than those obtained without RTA. By considering the model of Al diffusion from AlGaAs barrier into GaAs QWs together with the result from photoluminescence (PL) measurement, Al diffusion coefficients were calculated. The Al diffusion coefficient due to PECVD SiN was estimated at about 3 x10(-17) cm(2)/s. It was possible to extract the effect of RTA on the QW disordering, which showed that the amount of the blue shift and the Al diffusion coefficient due only to RTA increases with SiN cap layer thickness as reported by Chi et al.(10))
Keywords: OUT-DIFFUSION; WAVE-GUIDE; LASERS; GAAS; FILMS